2020
DOI: 10.1111/cpr.12956
|View full text |Cite
|
Sign up to set email alerts
|

Advances in mesenchymal stem cell transplantation for the treatment of osteoporosis

Abstract: Osteoporosis is a systemic metabolic bone disease with characteristics of bone loss and microstructural degeneration. The personal and societal costs of osteoporosis are increasing year by year as the ageing of population, posing challenges to public health care. Homing disorders, impaired capability of osteogenic differentiation, senescence of mesenchymal stem cells (MSCs), an imbalanced microenvironment, and disordered immunoregulation play important roles during the pathogenesis of osteoporosis. The MSC tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
144
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(149 citation statements)
references
References 162 publications
(254 reference statements)
2
144
0
3
Order By: Relevance
“…Finally, BMSCs and adipose stem cells are considered to have multidirectional differentiation and sustained proliferation capabilities in the treatment of bone loss in osteoporosis (93). BMSCs and breast cancer stem cells have also been reported for breast cancer (94).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, BMSCs and adipose stem cells are considered to have multidirectional differentiation and sustained proliferation capabilities in the treatment of bone loss in osteoporosis (93). BMSCs and breast cancer stem cells have also been reported for breast cancer (94).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Many studies have demonstrated that mesenchymal stem cells (MSCs) possess the potential for multidirectional differentiation and can be applied as potential donor cells for osteoporosis. 5,6 MSCs include adipose-derived stem cells (ADSCs), human umbilical cord mesenchymal stromal cells (hUC-MSCs), and bone marrow mesenchymal stem cells (BMSCs). 7 Among these three types of MSCs, ADSCs are most easily obtained and have low immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The decreased ability of osteogenic potential of osteoblasts from MSCs is the major risk of OP [ 10 ]. Thus, promoting osteogenic differentiation is an important strategy to enhance bone mineral density and slow the development of OP [ 11 ]. So far, teriparatide is one of the most effective agents to improve the osteogenic promotion drugs in clinic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%